Durability of concrete structures J.M.P.Q. Delgado - Delgado, Joao M. P. Q.
This book provides a collection of recent research works, related to structural stability and durability, service life, reinforced concrete structures, recycled materials, and sustainability with endogenic materials. Intended as an overview of the current state of knowledge, the book will benefit scientists, students, practitioners, lecturers and other interested parties. At the same time, the topics covered are relevant to a variety of scientific and engineering disciplines, including civil, materials and mechanical engineering."